A Highly Sensitive Visible-Light Photoelectrochemical Sensor for Pentachlorophenol Based on Synergistic Effect of 2D TiO2 Nanosheets and Carbon Dots. Issue 4 (2nd March 2020) - Fu, Xu-Cheng; Zhang, Jian; Gan, Wei; Bao, Lei
Abstract : A new visible-light photoelectrochemical (PEC) sensor based on 2D graphene-like TiO2 nanosheets and carbon dots nanocomposites modified glassy carbon electrode (TiO2 NSs/C-dots/GCE) is developed for pentachlorophenol (PCP) detection. The 2D TiO2 NSs and C-dots are both synthesized by one-step solvothermal methods and the TiO2 NSs/C-dots nanocomposites are prepared by a simple physical mixing method. The C-dots could effectively reduce the recombination of electrons and holes in the nanocomposites, improve the excitation conversion efficiency in visible-light area, and thus remarkably amplify the PEC signal. The PEC signal for PCP at the TiO2 NSs/C-dots/GCE sensor is about 11-times and 3.2-times larger than that at the C-dots/GCE and TiO2 NSs/GCE, respectively. The TiO2 NSs/C-dots/GCE sensor exhibits a wide linear proportion to the PCP concentration in the range from 0.1 to 4.5 nM with a detection limit of 0.05 nM (3S N −1 ). Moreover, the TiO2 NSs/C-dots/GCE sensor also shows high selectivity, excellent stability, and good repeatability in PCP determination. Furthermore, the TiO2 NSs/C-dots/GCE sensor is further applied to determinate PCP in practical water samples.